Distribution and habitat preferences of the Southern Antpipit (Corythopis delalandi) in the Austral Yungas of Bolivia and Argentina - Álvarez, María Eva (2007)
The currently known distribution of the Southern Antpipit (Corythopis delalandi) ranges from southern Brazil to eastern Paraguay, northeastern Argentina and east of Bolivia (Ridgely & Tudor 1994, Fitzpatrick 2004). According to the most recent review of the Tyrannidae family, this species is distributed towards the east of the department of Santa Cruz in Bolivia (Fitzpatrick 2004), where it has been found in gallery forests and lowland evergreen forests from 400 to 700 m (Hennessey et al. 2003). Although Narosky & Yzurieta (1987) considered this species as “occasional or with doubts” for northwestern Argentina in the last revised edition of their book, they excluded it from the region (Narosky & Yzurieta 2003). Mazar Barnett & Pearman (2001) do not consider the Southern Antpipit as a species characteristic of the Austral Yungas, but they include it as “accidental, registered only few times or with historical records”. Other general works on Argentinean avifauna do not mention this species for northwestern Argentina. Here we report new distribution records of the Southern Antpipit for the Austral Yungas in southern Bolivia and northwestern Argentina and we analyze its habitat preferences in this area.